Effectiveness and Quality of Life with Montelukast in Asthma – A double-blind randomized control trial: Effectiveness and Quality of Life with Montelukast in Asthma - Ullah Baig, Mirza Saif; Khan, Rashid Ahmed; Khan, Kamran; Rizvi, Nadeem (Pakistan Journal of Medical Sciences, 2019)
Objective: To determine the role of montelukast – a leukotriene receptor antagonist (LTRA) – in improving the quality of life (QOL) and asthma control of adult patients with mild to moderate persistent asthma.Methods: Randomized, double-blind, placebo-controlled, non-crossover trial was conducted from March 2017 till November 2018 in three hospitals of Karachi and Hyderabad. Adults of age 15 years or more with mild to moderate persistent asthma. Treatment group was administered tablet montelukast 10mg once daily; the other group was given a similar looking placebo; as an adjuvant to the current medication. QOL was assessed with Asthma Quality of Life Questionnaire – Standard (AQLQ-S) before and after the treatment. Asthma control was monitored via Asthma Control Test (ACT).Results: After 4 weeks, the mean ± SD of overall QOL on AQLQ-S improved from 3.74±0.88 to 5.06±0.89 for montelukast group and from 3.58±0.92 to 4.71±0.97 for placebo group (p=0.02). The improvement in sub-domains of symptoms, activity, and emotional functions was not significant; however, the sub-domain “environmental stimuli” significantly improved with 5.06±0.89 for montelukast group and 4.71±0.97 for placebo group (p=0.02). The mean ± SD of ACT, after four weeks, for montelukast group was 18.19±2.91 and for placebo group 17.28±3.36. Only on ACT, Montelukast did not show any statistically insignificant results.Conclusion: The role of montelukast in improving QOL of adult patients with mild to moderate persistent asthma is quite beneficial. It improves patient quality of life. It has the ease of once daily oral administration and also eradicates side effects associated with long-term adherence to steroids.doi: https://doi.org/10.12669/pjms.35.3.42How to cite this:Baig S, Khan RA, Khan K, Rizvi N. Effectiveness and Quality of Life with Montelukast in Asthma – A double-blind randomized control trial. Pak J Med Sci. 2019;35(3):731-736. doi: https://doi.org/10.12669/pjms.35.3.42This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.